2020
DOI: 10.7150/thno.45211
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroartemisinin ameliorates psoriatic skin inflammation and its relapse by diminishing CD8+ T-cell memory in wild-type and humanized mice

Abstract: Conventional immunosuppressants cause side effects and do not prevent the recurrence of autoimmune diseases. Moreover, they may not inhibit autoimmunity mediated by pathogenic memory T-cells. Dihydroartemisinin (DHA) has been shown to regulate autoimmunity. However, it remains unknown whether DHA impacts psoriasis and its recurrence. The objective of this study was to determine therapeutic effects of DHA on psoriasis and its relapse as well as its underlying mechanisms. Methods: We esta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 61 publications
1
33
0
Order By: Relevance
“…There is a growing appreciation that the activity of the nervous system plays an active role in various skin diseases, including psoriasis 5 , 7 , 8 , 11 , 12 , 50 . However, most of the emerging therapies exclusively target immune signaling with various anti-inflammatory drugs 54 , 55 and monoclonal antibodies against single pro-inflammatory cytokines 56 . Monoclonal antibodies have greatly advanced the clinical management of psoriasis, but not all patients are responsive to these treatments that can be expensive over prolonged periods, lead to unwanted effects such as immunosuppression, and occasionally even aggravate the disease 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing appreciation that the activity of the nervous system plays an active role in various skin diseases, including psoriasis 5 , 7 , 8 , 11 , 12 , 50 . However, most of the emerging therapies exclusively target immune signaling with various anti-inflammatory drugs 54 , 55 and monoclonal antibodies against single pro-inflammatory cytokines 56 . Monoclonal antibodies have greatly advanced the clinical management of psoriasis, but not all patients are responsive to these treatments that can be expensive over prolonged periods, lead to unwanted effects such as immunosuppression, and occasionally even aggravate the disease 57 , 58 .…”
Section: Discussionmentioning
confidence: 99%
“…However, in terms of immunomodulatory effects of ARTs, tremendous progress has been made during the last five to six years. We have recently demonstrated that dihydroartemisinin, an artemisinin derivative, ameliorates psoriatic skin inflammation and its relapse by selectively diminishing memory CD8+ T cells ( 11 ). In this review, we summarize recent studies that have explored the anti-inflammatory and immunomodulatory effects of ARTs on autoimmune diseases and allograft rejection as well as the mechanisms underlying their actions.…”
Section: Introductionmentioning
confidence: 99%
“…IMQ, a ligand of TLR-7/8, induces psoriasis-like dermatitis in mouse mimicking human psoriasis pathogenesis and systemic inflammation, including elevated levels of IL-23/IL-17A-Th17 axis pro-inflammatory cytokines and chemokines 34 - 36 . We analyzed the amino acid profiles in the IMQ-induced psoriasis-like dermatitis mouse model by amino acid-targeted metabolomics.…”
Section: Resultsmentioning
confidence: 99%